Upaya POLSEKTA Sukasari dalam Menindak Pelaku Balap Liar di Jalanan Kota Bandung - Krisyanto, Naia Kaiela Kriska Davina Malva Aulia Putri; Mustaqimah, Nurin Dilla; Razaan, Darell Jhoi; haq, Randika Nazal Dliyaul (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Illegal street racing in Bandung City, particularly in the Sukasari Police Sector area, remains a persistent issue that disrupts public order and endangers community safety. This study aims to identify the factors that contribute to the rise of illegal street racing, the legal basis used in handling such cases, and the social impacts that emerge. The research employs a qualitative descriptive approach through interviews with IPDA M.H as the key informant to gain an in-depth understanding of the phenomenon.The findings indicate that illegal street racing is driven by the influence of small youth groups, the desire for excitement, vehicle modification hobbies, and the need for social recognition. This activity often evolves into gambling practices and traffic violations that contravene the provisions of Law No. 22 of 2009. The Sukasari Police Sector implements repressive strategies through field operations, ticketing, and vehicle confiscation, as well as preventive strategies through educational programs and community outreach, especially targeting students.However, these efforts face several challenges, such as limited personnel, frequently shifting race locations, and the rapid communication networks among participants that allow them to evade police operations. Therefore, stronger collaboration between law enforcement, educational institutions, and the community is needed to effectively reduce illegal street racing in a sustainable manner.